Challenges and Opportunities for the Mission of the Churches in Indonesia in the Postmodern Era - Megawati ZAINAL (Indonesia Strategic Sustainability, 2022)
Postmodernism is a very controversial term. On the one hand, this term is often used cynically and mockingly. However, in reality, the term has attracted the wider community's interest even outside the academic world. Indeed the term has shown that it can articulate several crises and the fundamental socio-cultural changes that we are currently experiencing. The distinctive character of modernism always tries to find the basis of 'knowledge' about 'what' reality is, namely by returning to the subject of knowing (understood psychologically and transcendentally). It is hoped that a 'certainty' can be found, which is very basic for human knowledge of 'reality', namely the imagined reality as an external reality. In contrast, in postmodernism, human understanding is then built based on the perspective of society with 'subjectivity' and 'language'. At this point, there is no absolute truth, so Postmodern must create its own mini-narrative to be a reference for its life. The Church as God's messenger and representative is present to provide direction and strengthen the voice of a sacred conscience to Postmodernism. The desire to make narratives is not led by wild feelings or intuition, but by reason that has been renewed continuously. The Church should accomplish this by relying fully on the sovereign authority of the subject of faith rather than relying on her own fragile and sin-distorted powers of reason.